Estudo do exchange bias em filmes finos de NiFe/FeMn (bicamadas) e NiFe/IrMn (multicamadas) - Silva, Oreci Escobar da (2016)
The Exchange Bias (EB) phenomenon consists of an interfacial exchange coupling between a ferromagnetic (FM) material and an antiferromagnetic (AFM) one and has as the main characteristics the rise of a unidirectional anisotropy and a rotational hysteresis (HR) in torque curves. In this work we have investigated the behavior of the magnetic behavior of systems presenting EB through magnetization curves, anisotropic magnetorresistance (AMR)and torque magnetometry. We have grown films, via magnetron sputtering, of NiFe/FeMn (bilayers) with different thickness of the FM layer and film structures of NiFe/IrMn/Ta with different repetitions of the basic s tructure. From the X-ray diffraction and reflectivity we have determined the preferential crystallographic growth direction, the thickness and the grain size of the studied samples. It was implemented at the Magnetism and Magnetic Materials Laboratory (LMMM) an apparatus to measure the AMR in two configurations: resistance as a function of the applied field angle and resistance as function of the field applied in a particular angle direction. To adjust the magnetization and AMR data we have used a phenomenological model for EB considering four energy terms: Zeeman, uniaxial, unidirectional and magnetostatic. The AMR curves have shown an asymmetry around 180º when measured at field smaller than the Bias one. According to the used model used, such asymmetry can be caused either by a misalignment between the anisotropy axes (uniaxial and unidirectional) or by a misalignment between the measurement current direction easy magnetization axis of the sample. It was not observed in the multilayers an increase on the uniaxial anisotropy dispersion with increasing on the trilayers number, as expected. In order to fit average torque curves, we have used an equation with two harmonic terms. The resulting parameters allow us to study the field evolution of the harmonic amplitudes Kθ e K2θ. In the multilayer system as higher total energy is, higher is the energy losses by HR. In bilayers system, the HR energy losses still increases even above the saturation field. Such behavior was associated to the configuration of interfacial spins and suggests the need of an additional contribution to total energy of the magnetic system.